me ajude pessoal por favor genteeeee é pra manhã dia 18-08-15
![1) (x^{2} -5x+3)+(-4 x^{2} -2x)=<br /><br />
2) (9 x^{2} -4x3-3)+(3 x^{2} -10)= 1) (x^{2} -5x+3)+(-4 x^{2} -2x)=<br /><br />
2) (9 x^{2} -4x3-3)+(3 x^{2} -10)=](https://tex.z-dn.net/?f=1%29++%28x%5E%7B2%7D+-5x%2B3%29%2B%28-4+x%5E%7B2%7D+-2x%29%3D%3Cbr+%2F%3E%3Cbr+%2F%3E%0A2%29+%289+x%5E%7B2%7D+-4x3-3%29%2B%283+x%5E%7B2%7D+-10%29%3D)
quem podera me ajuda agradeçoooo
Soluções para a tarefa
Respondido por
1
a)
= x² - 5x + 3 + ( - 4x² - 2x)
= x² - 5x + 3 - 4x² - 2x
= x² - 4x² - 5x - 2x + 3
= - 3x² - 7x + 3
b)
= 9x² - 4x³ - 3 + 3x² - 10
= - 4x³ + 9x² + 3x² - 3 - 10
= - 4x³ + 12x² - 13
= x² - 5x + 3 + ( - 4x² - 2x)
= x² - 5x + 3 - 4x² - 2x
= x² - 4x² - 5x - 2x + 3
= - 3x² - 7x + 3
b)
= 9x² - 4x³ - 3 + 3x² - 10
= - 4x³ + 9x² + 3x² - 3 - 10
= - 4x³ + 12x² - 13
Perguntas interessantes
Sociologia,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás